Conditional ablation of the choroideremia gene causes age-related changes in mouse retinal pigment epithelium. - Silène T Wavre-Shapton; Tanya Tolmachova; Mafalda Lopes da Silva; Clare E Futter; Miguel C Seabra (PLoS ONE)
The retinal pigment epithelium (RPE) is a pigmented monolayer of cells lying between the photoreceptors and a layer of fenestrated capillaries, the choriocapillaris. Choroideremia (CHM) is an X-linked progressive degeneration of these three layers caused by the loss of function of Rab Escort protein-1 (REP1). REP1 is involved in the prenylation of Rab proteins, key regulators of membrane trafficking. To study the pathological consequences of chronic disruption of membrane traffic in the RPE we used a cell type-specific knock-out mouse model of the disease, where the Chm/Rep1 gene is deleted only in pigmented cells (Chm(Flox), Tyr-Cre+). Transmission electron microscopy (TEM) was used to quantitate the melanosome distribution in the RPE and immunofluorescent staining of rhodopsin was used to quantitate phagocytosed rod outer segments in retinal sections. The ultrastructure of the RPE and Bruch's membrane at different ages was characterised by TEM to analyse age-related changes occurring as a result of defects in membrane traffic pathways. Chm/Rep1 gene knockout in RPE cells resulted in reduced numbers of melanosomes in the apical processes and delayed phagosome degradation. In addition, the RPE accumulated pathological changes at 5-6 months of age similar to those observed in 2-year old controls. These included the intracellular accumulation of lipofuscin-containing deposits, disorganised basal infoldings and the extracellular accumulation of basal laminar and basal linear deposits. The phenotype of the Chm(Flox), Tyr-Cre+ mice suggests that loss of the Chm/Rep1 gene causes premature accumulation of features of aging in the RPE. Furthermore, the striking similarities between the present observations and some of the phenotypes reported in age-related macular degeneration (AMD) suggest that membrane traffic defects may contribute to the pathogenesis of AMD.